THE EFFECT OF MULTI-MICRONUTRIENT SUPPLEMENTATION ON HEMOGLOBIN STATUS AMONG PREGNANT WOMEN AT BULANGO TIMUR PUBLIC HEALTH CENTER, BONE BOLANGO DISTRICT - Fitriana Bidul; Srikit S Nurkamiden; Adnan Engelen (Journal of Health, Technology and Science (JHTS), 2026)
Maternal anemia remains a major public health problem during pregnancy and is often associated with multiple micronutrient deficiencies. Multiple micronutrient supplementation (MMS) has been recommended to improve maternal nutritional status and hemoglobin levels. This study aimed to determine the effect of MMS on hemoglobin status among pregnant women at Bulango Timur Public Health Center, Bone Bolango District. A quantitative study using a pre-experimental one-group pretest–posttest design was conducted based on secondary data from maternal health records. A total of 18 pregnant women who received MMS supplementation were included using total sampling. Hemoglobin status before and after supplementation was assessed and analyzed using descriptive statistics and the Wilcoxon Signed-Rank Test with a significance level of 0.05. Before MMS supplementation, 72.2% of participants had abnormal hemoglobin status, while 27.8% had normal status. After supplementation, the proportion of normal hemoglobin status increased to 77.8%, whereas abnormal status decreased to 22.2%. The mean hemoglobin status score increased from 1.278 ± 0.461 before supplementation to 1.778 ± 0.428 after supplementation. The Wilcoxon Signed-Rank Test showed a statistically significant difference between pre- and post-supplementation hemoglobin status (Z = 2.496, p = 0.013). MMS supplementation was significantly associated with improved hemoglobin status among pregnant women and may serve as a useful strategy for reducing anemia risk during pregnancy.